MODELING OF THIN SAWS NOISE EMISSION - Arine A. Avakyan; Artem E. Litvinov; Igor S. Morozkin (Вестник Донского государственного технического университета, 2018)
Noise level dependences of thin saws of the metal-cutting machines and woodworkers are resulted. It is shown that abatement of noise in the source can be achieved by the rational choice of the vibration cushioning specifications for the vibration protection systems.